Structural, electronic, and elastic properties of orthorhombic NaB3H8: A first-principles investigation. (September 2019) - Li, Shina; Quan, Hao; Yu, Suye
Abstract: First-principles calculations are used to study the structural, electronic, and elastic properties of the orthorhombic Pmn 21 -NaB3 H8 hydrogen storage material. The obtained lattice parameters (a = 7.8546 Å, b = 5.7887 Å, c = 4.5595 Å) within PBE functional are in good agreement with the experimental data. It has a volumetric hydrogen density of 128.16 kg/m 3 . The structural and electronic properties indicate that H in [BH2 ](12) group is most likely to be released firstly when the Pmn 21 -NaB3 H8 decomposes. The elastic moduli, Poisson's ratio, Debye temperature, and elastic wave velocities of Pmn 21 -NaB3 H8 are successfully derived from the independent single-crystal elastic constants. Based on our results, the insulator Pmn 21 -NaB3 H8 with large band gaps of 5.8 eV exhibits mechanical stability and ductility (B/G = 2.91). The obtained elastic anisotropy indexes, directional dependent linear compressibility, and Young's modulus show that the Pmn 21 -NaB3 H8 has obvious anisotropic mechanical properties. Highlights: Properties of Pmn 21 -NaB3 H8 are studied by using first-principles method. The relaxed structure, volumetric hydrogen density, and energy gap are obtained. The order of hydrogen release is analyzed when Pmn 21 -NaB3 H8 decomposes. The stability, ductility/brittleness, and elastic anisotropy are discussed. Debye temperature and sound velocities are evaluated from elastic constants.